Complete resection of the superficial femoral artery and superficial femoral vein due to forceful trauma: a case report
BACKGROUND: The incidence of superficial femoral artery trauma with or without involvement of superficial femoral vein, in the absence of organ injury or fractures, is rare. We present a case of superficial femoral artery and vein resection caused by high-energy blunt trauma. CLINICAL CASE: A 60-year-old male was transferred to our hospital due to forceful trauma of the superficial femoral artery and vein. The injured portion of the artery was resected, and a reversed ipsilateral great saphenous vein graft interposition was performed. The superficial femoral vein was ligated. No post-operative complications were noted, and the patient was discharged three weeks after the operation without any relevant sequelae CONCLUSION: This case report highlights the clinical presentation, diagnostic workup, management, and outcomes of traumatic blunt injuries to the femoral vessels.